Planejamento tributário : estudo de caso em uma pizzaria - Figueiredo, Itanara da Silva (2022)
Tax planning is an important tool for management control and especially for decision-making, since its main objective is to help the company to reduce the amount of taxes in a lawful manner. The present case study in a pizzeria aims to identify the most economical tax regime for the year 2023, based on calculations for the Real Profit, Presumed Profit and Simples Nacional regimes. This work began with a theoretical basis through bibliographies on the subject presented. Since the methodology to be used was a case study approaching in a descriptive way the characteristics and finally through a quantitative analysis it was possible to measure the amount due for each tax for the tax regimes studied. With this, it made it possible to identify and compare the annual tax burden due if the company opts for each tax regime, where for Real Profit it will be R$ 63,098.05; for Presumed Profit R$ 64,567.66 and for Simples Nacional R$ 16,826.94; demonstrating that Simples Nacional is the best option. Having also the analysis of the possible scenarios for 2023, both optimistic and pessimistic, it reinforces that Simples Nacional should be chosen because it generates a lower tax burden for the company.